2014
DOI: 10.1063/1.4904737
|View full text |Cite
|
Sign up to set email alerts
|

Design of set-point weighting PIλ + Dμ controller for vertical magnetic flux controller in Damavand tokamak

Abstract: In this paper, a simple method is presented for tuning weighted PI(λ) + D(μ) controller parameters based on the pole placement controller of pseudo-second-order fractional systems. One of the advantages of this controller is capability of reducing the disturbance effects and improving response to input, simultaneously. In the following sections, the performance of this controller is evaluated experimentally to control the vertical magnetic flux in Damavand tokamak. For this work, at first a fractional order mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…By equating HðsÞ in (18) with H desired ðsÞ in (19), the proportional gain of the FOPID controller ðk p Þ and the filter denominator coefficient ðhÞ are respectively obtained as (6) for different values of commensurate order a depicted in w-plane where w ¼ s a [51]. Therefore, according to relations (15)- (17), (20), and (21), the parameters of the FOPID controller, the set-point weight, and the constant coefficient of fractional order filter can be determined uniquely.…”
Section: Tuning Procedures For the Swfopid Controllermentioning
confidence: 99%
See 4 more Smart Citations
“…By equating HðsÞ in (18) with H desired ðsÞ in (19), the proportional gain of the FOPID controller ðk p Þ and the filter denominator coefficient ðhÞ are respectively obtained as (6) for different values of commensurate order a depicted in w-plane where w ¼ s a [51]. Therefore, according to relations (15)- (17), (20), and (21), the parameters of the FOPID controller, the set-point weight, and the constant coefficient of fractional order filter can be determined uniquely.…”
Section: Tuning Procedures For the Swfopid Controllermentioning
confidence: 99%
“…It has been shown that the fractional order controllers are more effective in some industrial applications [12,15,20]. Also, this type of controllers have been applied in a wide range of practical applications; such as control of magnetic flux in tokamak machine [19], heat flow platform [20], hexapod robot [37], permanent magnetic synchronous motors [38], and power electronic buck converters [39].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations